2005
DOI: 10.1007/s00264-005-0656-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary malignant bone tumours of the distal tibia

Abstract: We treated 15 patients with primary malignant bone tumours of the distal tibia of which 14 were treated by limb salvage surgery. Reconstructions were done by allografts with or without microvascular fibula transfer, by bone transport, by fibula transfer alone or by endoprosthetic replacement. The most successful methods were bone transport and endoprosthetic replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 17 publications
2
54
0
1
Order By: Relevance
“…Other series [12, 16, 18] have had similar results between limb salvage and amputation for osteosarcoma of the distal tibia. However, the sample sizes in those studies are relatively smaller and comparisons were performed mostly between different types of reconstructions after limb salvage.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Other series [12, 16, 18] have had similar results between limb salvage and amputation for osteosarcoma of the distal tibia. However, the sample sizes in those studies are relatively smaller and comparisons were performed mostly between different types of reconstructions after limb salvage.…”
Section: Discussionmentioning
confidence: 71%
“…Historically, it has been very difficult to achieve satisfactory oncologic results and function with limb salvage in this anatomic location because of its particular challenges [12, 16, 18]. It has been reported that transtibial amputation provides a low risk of local recurrence and satisfactory function [2].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated survival rate was obtained with osteoarticular allograft (77 %), similar to other allograft types; however, they presented the highest complication rate (44 %) including fractures, infections local recurrences, and fractures. Reconstruction of defects after tumor resections of the distal tibia has been performed using allografts [33,34], autografts [35,36], and endoprostheses [37,38], although the reports included limited number of cases due to its low incidence [39,40]. Of the eight distal tibia OA in our series, five had complications: three articular failure (two required arthrodesis), one fracture and one local recurrence (required amputation).…”
Section: Discussionmentioning
confidence: 95%
“…But conflicting results have been reported regarding survival and function after limb salvage and amputation for patients with low-grade osteosarcoma of the distal tibia. [13,14] Several studies reported the survival rates after limb-salvage range from 100% to 50% at 6-288 months, [15,16] whereas those for amputation range from 100% to 84% at 36-60 months. [4,17] Thus, whether the relapse, 5-year survival and metastasis the same or not between limb-salvage and amputation in the treatment of patients with limited stage EnnekingⅡpathologic fracture osteosarcoma was not known.…”
Section: Discussionmentioning
confidence: 99%